Of grazing adjustment, from cattle farmers to consumers: an agroindustrial chain approach - Simeone, A.; Beretta, Virginia (Cuban Journal of Agricultural Science, 2023)
The main characteristics of the beef production chain are set out in order to identify the chain links that hamper its development. The Uruguayan experience is shown. The importance of the time devoted to the productive process as to biological particularities of the biological cycle of beef production and the multiplicity of products generated during the industrial stage are two of the traits that should be taken into account to design a strategy addressed to the development of this process. The application of production technologies that fasten cattle growth and fattening, as well as market differentiation to efficiently sell products (high- and low-quality meat cuts) and byproducts (hide, viscera, fat) are two alternatives that encourage beef production. The strategy implemented in Uruguay has permitted a significant reduction in slaughter age by including supplementation in enclosure feeding for cattle production systems. The development of a public policy based on obtainment of sanitary status, on total cattle traceability, and on an electronic information system in the beef industry has allowed gaining international confidence, reflected in entering the most demanding markets, besides fulfilling the domestic market intake. Key words: cattle, industry, markets, case study.